(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
Calderón, like Omar Cáceres and many others, is a painful residue that destabilizes the endeavor of authors and mediators to float in the literary landscape seeking interpretative canons ("hermeneutical caricatures") that inevitably produce unjust and disastrous concealments. A poet of extremely peculiar lyrical production within his context and generation, he was forgotten like so many others who pass fleetingly on the surface of the literary consciousness of the system, and he is a clear example of an amnesiac operation that undermines the life and work of many, varied, and qualified Chilean poets, among whom are Romeo Murga, Omar Cáceres, Alberto Rojas Jiménez, and Carlos de Rokha (note).